Social Media Impact: Influencing Customer Purchase Decisions - A. S Pragathi, G. Hemanth Reddy, (European Economic Letters (EEL), 2024)
This study examines the influence of social media content and engagement strategies on consumer purchasing behaviour. Two hypotheses are investigated: (1) the positive correlation between exposure to social media content and purchase likelihood, and (2) the impact of visual content emphasis and user-generated reviews on consumer purchase decisions. Regression analyses were conducted on a sample dataset comprising demographic variables and measures of social media engagement. Results indicate a significant positive relationship between exposure to social media content and purchase likelihood, highlighting the influential role of social media platforms in shaping consumer behaviour. Additionally, platforms emphasizing visual content and user-generated reviews were found to have a greater impact on influencing purchase decisions compared to text-based platforms. However, gender was not found to significantly influence the impact of social media content on purchase decisions. Future research should focus on expanding the study to include a larger and more diverse sample, exploring additional factors such as brand perception and platform-specific features, and conducting longitudinal studies to track evolving social media trends. Overall, this research contributes to our understanding of effective social media marketing strategies and their impact on consumer behaviour.